SUMF1 enhances sulfatase activities in vivo in five sulfatase deficiencies - Fraldi, Alessandro (Portland Press Ltd., 2007)
Sulfatases are enzymes that hydrolyse a diverse range of sulfate esters. Deficiency of lysosomal sulfatases leads to human diseases characterized by the accumulation of either GAGs (glycosaminoglycans) or sulfolipids. The catalytic activity of sulfatases resides in a unique formylglycine residue in their active site generated by the post-translational modification of a highly conserved cysteine residue. This modification is performed by SUMF1 (sulfatase-modifying factor 1), which is an essential factor for sulfatase activities. Mutations in the SUMF1 gene cause MSD (multiple sulfatase deficiency), an autosomal recessive disease in which the activities of all sulfatases are profoundly reduced. In previous studies, we have shown that SUMF1 has an enhancing effect on sulfatase activity when co-expressed with sulfatase genes in COS-7 cells. In the present study, we demonstrate that SUMF1 displays an enhancing effect on sulfatases activity when co-delivered with a sulfatase cDNA via AAV (adeno-associated virus) and LV (lentivirus) vectors in cells from individuals affected by five different diseases owing to sulfatase deficiencies or from murine models of the same diseases [i.e. MLD (metachromatic leukodystrophy), CDPX (X-linked dominant chondrodysplasia punctata) and MPS (mucopolysaccharidosis) II, IIIA and VI]. The SUMF1-enhancing effect on sulfatase activity resulted in an improved clearance of the intracellular GAG or sulfolipid accumulation. Moreover, we demonstrate that the SUMF1-enhancing effect is also present in vivo after AAV-mediated delivery of the sulfamidase gene to the muscle of MPSIIIA mice, resulting in a more efficient rescue of the phenotype. These results indicate that co-delivery of SUMF1 may enhance the efficacy of gene therapy in several sulfatase deficiencies.